2011
DOI: 10.17744/mehc.33.2.8t2q386453231312
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Treatment Compliance Among Male Batterers: Motivators to Get Them in the Door and Keep Them in the Room

Abstract: A clinical focus on what motivates batterers to enter counseling might improve the prognosis for their treatment compliance. We discuss motivators to get them in the door (treatment engagement) and keep them in the room (treatment compliance). Once they are invested in the therapeutic process, they might successfully break their pattern of abuse, learn new coping skills, and adopt healthy behaviors to sustain successful, nonviolent intimate relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…However, the relationship between denial, minimization and blame, and recidivism is not well understood (Henning & Holdford, 2006; Lila et al, 2008). Furthermore, there is limited research on how BIPs’ overcome denial to achieve accountability with perpetrators (Catlett et al, 2010; Chovanec, 2012), or what practices (e.g., length of time for treatment, treatment modality; Muldoon & Gary, 2011) are best for overcoming resistance. Our study suggests that perpetrator “buy in” to programs is perhaps dependent on BIPs’ ability to overcoming resistance, something that may prove difficult and require more time than programs have with clients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between denial, minimization and blame, and recidivism is not well understood (Henning & Holdford, 2006; Lila et al, 2008). Furthermore, there is limited research on how BIPs’ overcome denial to achieve accountability with perpetrators (Catlett et al, 2010; Chovanec, 2012), or what practices (e.g., length of time for treatment, treatment modality; Muldoon & Gary, 2011) are best for overcoming resistance. Our study suggests that perpetrator “buy in” to programs is perhaps dependent on BIPs’ ability to overcoming resistance, something that may prove difficult and require more time than programs have with clients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite research suggesting that developing relationships within and outside of PAIPs may be a necessary predecessor in changing the behaviors of partner violent men (Sheehan et al, 2012), traditional practice has discouraged outside socialization in fear of possible collusion of members that could lead to problems like unchallenged victim blaming. Facilitators tend to have some degree of autonomy in PAIPs, which has resulted in reports of some programs establishing buddy systems amongst group members or encouraging former participants to mentor (sponsor) group members (Muldoon & Gary, 2011). While concerns about the possibility of sponsor-mentee collusion to encourage violence may deserve attention (Almeida & Bograd, 1991), the present study provides some empirical support for the potential benefits of positive peer relationships and contrast the traditional use of male peer social support theory, which focuses on the reinforcement of negative behaviors (DeKeseredy & Schwartz, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve this, this approach focuses on the promotion of meaningful targets for the participant. This intervention model and other successful strategies aiming to increase motivation to change and adherence to treatment, such as the motivational interview, the therapeutic alliance, or proactive retention techniques, are being recognized by a growing number of scholars as important paths to improve the effectiveness of intervention programs for IPVOs (Carbajosa et al, 2013;Kistenmacher & Weiss, 2008;Lee et al, 2007;Muldoon & Gary, 2011;Musser & Murphy, 2009;Taft & Murphy, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As for the second alternative, two recent reviews have identified a number of intervention strategies that promote positive changes among IPVOs (Eckhardt et al, 2006;Saunders, 2008). These strategies include the motivational interview, the therapeutic alliance, and retention techniques, which appear to increase IPVOs' motivation and adherence to treatment and promote their active participation in their own change (Carbajosa, Boira, & Tomás-Aragonés, 2013;Kistenmacher & Weiss, 2008;Lee et al, 2007;Muldoon & Gary, 2011;Musser & Murphy, 2009). These new approaches are based on the notion that the intervention success can be increased by applying strategies which help the participants to commit themselves to the intervention and to understand that this is aimed to increase their wellbeing and psychological adjustment (Langlands et al, 2009;Taft & Murphy, 2007).…”
Section: Effectiveness Of Intervention Programs For Ipvosmentioning
confidence: 99%
See 1 more Smart Citation